APPLICATION OF FLIPPED LEARNING MODEL AS IMPLEMENTATION OF BASIC MANAGEMENT FUNCTIONS - Januari Ayu Fridayani; Fransisca Desiana Pranatasari (Management and Sustainable Development Journal, 2020)
This study explains how the basic functions of management—planning, organizing, leading and controlling (POLC)—are packaged in a flipped learning model. The basic functions of management, in general, are introduced at the beginning of lectures and become the basis for further learning in Management Department. As basic course material, the learning process of basic functions management must be arranged systematically and interestingly to motivate students to involve in the next learning materials enthusiastically. Through a case study on the subject of Organizational Management in the Management Department, Faculty of Economics, Sanata Dharma University, this study provides an overview of the learning process of flipped learning to introduce the basic functions of management to students. By utilizing description qualitative approach, this study shows that the flipped learning model can be one of the prospective alternative learning model in implementing basic management functions, both for lecturers and students. Keywords: basic functions of management, learning models, flipped learning Abstrak Studi ini menjelaskan bagaimana fungsi dasar manajemen—planning, organizing, leading dan controlling (POLC)—dikemas dalam suatu model flipped learning. Fungsi dasar manajemen, pada umumnya, dikenalkan pada masa awal perkuliahan dan menjadi basis untuk pembelajaran selanjutnya pada program studi manajemen. Sebagai materi kuliah dasar, proses pembelajaran terkait fungsi dasar manajemen harus disusun secara sistematis dan menarik untuk memotivasi mahasiswa mengikuti materi-materi pembelajaran selanjutnya dengan antusias. Melalui studi kasus pada mata kuliah Manajemen Organisasi di Program Studi Manajemen, Fakultas Ekonomi Universitas Sanata Dharma, studi ini memberikan gambaran proses pembelajaran flipped learning untuk mengenalkan fungsi dasar manajemen kepada mahasiswa. Dengan memanfaatkan pendekatan deskripsi kualitatitif, penelitian ini menunjukkan bahwa model flipped learning dapat menjadi salah satu alternatif bentuk pembelajaran yang prospektif dalam mengimplementasikan fungsi dasar manajemen, baik bagi dosen maupun mahasiswa. Kata kunci: fungsi dasar manajemen, model pembelajaran, flipped learning